Psychoanalytic Criticism of Dr. Van Helsing in the Novel Dracula - K.C., Chandra Bahadur (Journal of Development Review, 2020)
Set in the backdrop of Gothic horror tradition, Bram Stoker’s novel Dracula (1897) intermixes with fondness of romance. It overtly describes the love of Dr. John Seward, Arthur Holmwood and Quiencey Morris to Lucy Westerna. The behaviuors that they show towards main female characters in the novel express their love to women. But Dr. Van Helsing, the leader of the heroes’ team, is presented as the inspiring figure who leads the band of the young people in a sacred ritual. He is from Amsterdam and we do not know anything about his family background except his insane wife who is now in “insane institution”. In the novel he is the character taken for granted as an all good personality. He is presented as the benevolent father figure who is panacea for the trouble wrenched youngsters. However, we can raise some questions on his behaviours. Is he solely an ascetic person? Is he not interested in love affairs with any woman? This paper attempts to analyze the behaviuors of Dr. Van Hesling from psychoanalytic perspective. This paper claims that there is the working of the unconscious at his love to the women so that he takes part in Dracula killing mission. By analyzing his behaviours from psychoanalytic perspective, he is a man unconsciously running after women. His behaviours express his unfulfilled sexual desire, a man with woman fixation.